A shadow fault detection method based on the standard error analysis of I-V curves. (December 2016) - Bressan, M.; El Basri, Y.; Galeano, A.G.; Alonso, C.
Abstract: Shading on photovoltaic (PV) modules induces disproportionate impacts on power production. This paper presents a fault detection method able to identify anomalies on PV systems such as shading problems. The presence of localized shading on PV modules leads to an overheating of the shaded PV cells despite the activation of by-pass diodes. The temperature increase reduces considerably PV module performances and its lifetime. The presented method uses a simple equation, which corresponds to the normalized error (DE) of the comparison between the I-V curve in normal operation and the I-V curve in shading condition. The first derivative calculation gives the area of the detection in function of the PV voltage of the module (DE/DV). This defines whether one or several PV cells dissipate power. This phenomenon essentially occurs in the case of non-uniform irradiance received on PV modules and could impact PV modules performances. The detection method is explained in detail through the study of specific shadows simulations on PV modules. The results are validated through experimental tests on PV modules. Highlights: Fault detection method identifying anomalies on PV systems such as shading problems. Overheating of shaded PV cells despite the activation of by-pass diodes (thermal test). Analysis of I-V curves in order to dissociate an homogenous shading of a non homogenous shading.